Fiscal Monitor, April 2017 : Achieving More with Less. (Fiscal Monitor; Fiscal Monitor ;, 2017)
This publication is a survey by the IMF staff, published twice a year, in the spring and fall, as part of the IMF's World Economic and Financial Surveys. The current issue analyzes the latest public finance developments, updates medium-term fiscal projections, and assesses policies aimed at placing public finances on a sustainable footing. An analytical chapter employs extensive firm-level data sets as well as new sources of data on tax policy and tax administration for advanced economies, emerging market economies, and low-income developing countries to assess the extent of resource misallocation within countries, focusing on how the design of the tax system may affect resource allocation.